Depression and self‐care in older adults with multiple chronic conditions: A multivariate analysis. (23rd April 2020) - Iovino, Paolo; De Maria, Maddalena; Matarese, Maria; Vellone, Ercole; Ausili, Davide; Riegel, Barbara
Abstract: Aims: To investigate the relationship between depression and self‐care behaviours in older individuals with multimorbidity. Design: Cross‐sectional study. Data were collected between April 2017 – June 2019. Methods: Patients were enrolled from community and outpatient settings and included if they were ≥65 years, affected by heart failure, diabetes mellitus or chronic obstructive pulmonary disease and at least another chronic condition. They were excluded if they had dementia and/or cancer. Patient Health Questionnaire‐9 was used to measure depression and Self‐Care of Chronic Illness Inventory was used to measure self‐care maintenance, monitoring, and management. The relationship between depression and self‐care was evaluated by performing two sets of univariate analyses, followed by multivariate and step‐down analyses. The second set was performed to control for the number of chronic conditions, age, and cognitive function. Results: The sample ( N = 366) was mostly female (54.2%), with a mean age of 76.4 years. Most participants (65.6%) had mild to very severe depressive symptoms. Preliminary analysis indicated a significant negative association between depression and self‐care maintenance and monitoring and a significant negative association between depression and multivariate self‐care. Step‐down analysis showed that self‐care maintenance was the only dimension negatively associated with depression, even after controlling for the number of chronic conditions, age, and cognitive function. Conclusion: In multimorbid populations, depression is more likely to be associated with self‐care maintenance than the other self‐care dimensions. Therefore, self‐care maintenance behaviours (e.g., physical activity and medication adherence) should be prioritized in assessment and focused on when developing interventions targeting depressed older adults with multimorbidity. Impact: The results of this study may help guide clinical practice. In patients with depressive symptoms, self‐care maintenance behaviours should be assessed first, as a potential first indicator of poor self‐care. Abstract : 目的: 探讨多种慢性疾病的老年患者的抑郁与自我护理行为的关系。 设计: 横断式研究。收集2017年4月至2019年6月期间的数据。 方法: 来自社区和门诊部, 年龄达到65岁以上, 患有心力衰竭、糖尿病或慢性阻塞性肺疾病和其他慢性疾病的患者。需要去除患有痴呆和/或癌症的患者。患者健康问卷‐9用于衡量抑郁水平, 而慢性病自我护理调查表用于衡量自我护理的维持、监测和管理水平。通过先进行两组单变量分析, 然后是多变量分析和阶梯分析, 评估抑郁与自我护理之间的关系。第二组用于对照慢性疾病的数量、年龄和认知功能。 结果: 样本( N = 366)以女性为主(54.2%), 平均年龄76.4岁。大多数受访者(65.6%)有轻度到非常严重的抑郁症状。初步分析表明, 抑郁与自我护理的维持和监测之间存在显著的负相关联系, 抑郁与多变量自我护理之间存在显著的负相关联系。阶梯分析则显示, 即使保持慢性病的数量、年龄和认知功能的相同性后, 自我护理的维持是与抑郁负相关的唯一衡量维度。 结论: 在患有多种疾病的人群中, 抑郁与自我护理维持的相关性比自我护理的其他衡量维度因素都高。因此, 在评估中应优先考虑自我护理的维持行为(如体育活动和药物治疗依从性), 并在针对患有多种疾病的抑郁症老年人制定介入治疗时予以重点关注。 影响: 本研究结果有助于指导临床实践。在具有抑郁症状的患者中, 应首先评估其自我护理的维持行为, 作为自我护理不良的潜在第一指标。